Digital Technology in Supporting Learning at SLB-A Yapti Makassar - ashdaq, muhammad; Aris, Valentino; Alam, Syamsu; Taufik, Muhammad; Ruslan, Andi; Jamil, Muhammad (Ininnawa : Jurnal Pengabdian Masyarakat, 2025)
This Community Service Activity was carried out between the Digital Business Study Program Service Team, Makassar State University in partnership with the Yapti Makassar Special School (SLB-A Yapti Makassar). The problem faced by service partners is the lack of digital skills possessed by blind students at SLB-A Yapti Makassar in carrying out the learning process. The activities carried out aim to increase the enthusiasm for learning and digital abilities of blind students at SLB-A Yapti Makassar. The training participants were eight students who were representatives of all students at SLB-A Yapti Makassar. Training methods include lectures, discussions, and practice in using digital platforms for learning. The results obtained from this activity include (a) Partners have enthusiasm and competence in learning using digital technology, (b) Partners gain literacy in using digital technology in learning, (c) Partners gain experience in practicing using digital technology in learning.